Fuzzy Approach on Horticulture Quality Standard Database - Mulyarto, Aunur R.; Sucipto, Sucipto (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
Horticulture quality characteristics are commonly defined in the uncertainty, vague and ambiguous forms. These can be a problem in designing database of horticulture quality standard. This research intended to develop a database system for horticulture quality characteristics that can handle the nature of quality characteristics data using fuzzy approach. Two main activities that were carried out are fuzzyfication of horticulture quality characteristics and designing database using fuzzy relational model. The results show that most of local fruits and vegetables have been standardized either in national scope using SNI (Indonesian National Standard) or local scope using market segmentation standard. For fuzzy variable, its fuzzy sets depend on the values of quality prerequisite for each quality grade. Conceptual design using Fuzzy Relational Database model involves five major entities, i.e. Categories, Comodities, Standard Type, Quality Standard, and Quality Criteria. To accommodate the fuzzy characteristics, a specific entity which is an extension entity (Fuzzy Set) was added. The transformation process into relational data model and table normalization produced seven related tables.Keywords: horticulture, quality, database, fuzzy logic